2003
DOI: 10.1103/physreve.67.057402
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear drift waves in electron-positron-ion plasmas

Abstract: It is suggested that low-frequency drift waves can play an important role in the dynamics of electron-positron plasmas comprising some concentration of ions. In the electromagnetic case the drift wave couples with the shear Alfvén wave in an electron-positron-ion plasma. The drift wave frequency can be very low in such plasmas depending on the concentration and density scale lengths of the plasma components. In the nonlinear regime these waves can give rise to dipolar vortices in both electrostatic and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…It is found that as the relativistic streaming velocities of the ions increases the amplitude of the solitons also increases. The propagation of shock waves in the weakly relativistic epi plasma has been studied in Shah and Saeed (2009). The authors noticed that the shock strength decreases as the parameters such as ion relativistic streaming factor, positron concentration are increased.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is found that as the relativistic streaming velocities of the ions increases the amplitude of the solitons also increases. The propagation of shock waves in the weakly relativistic epi plasma has been studied in Shah and Saeed (2009). The authors noticed that the shock strength decreases as the parameters such as ion relativistic streaming factor, positron concentration are increased.…”
mentioning
confidence: 98%
“…Nejoh (1997) has used pseudo-potential approach to study the nonlinear propagation of ion acoustic waves in epi plasmas. The study of drift waves in epi plasma, and predictions about the existence of dipolar vortices for both the electrostatic and electromagnetic cases in the limits of very low frequency are presented by Saleem et al (2003). Mahmood and Akhter (2008) studied the influence of adiabatic ion temperature, positron concentration on the amplitude of electron density hump in magnetized epi plasmas through the sagdeev potential approach.…”
mentioning
confidence: 99%
“…However, for pair plasmas, the low-frequency modes associated with motions of ions are absent. 18 Due to the unique features of pair plasmas, various work has been done to investigate linear and nonlinear collective wave modes, [19][20][21][22][23][24][25][26] as well as the Fokker-Planck study, 27 fast reconnection, [28][29][30][31][32] etc., in pair plasmas. However, when a pair plasma is extremely dense and/or is cooled to an extremely low temperature, the de Broglie wavelength of the charge carriers ͓viz., B = ប / ͑mv T ͒, where ប is the Planck constant divided by 2, m is the particle mass, and v T is the thermal velocity͔ becomes comparable to the typical interparticle distance d = n −1/3 ͑n is the particle number density͒; quantum effects are expected to play a significant role in the behavior of charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] It has been shown that the drift wave frequency can be very much reduced by the presence of positrons. 9 In this Brief Communication, we analyze the linear dispersion equation and obtain a modified Rayleigh condition for the instability of drift waves in the presence of shear flow in the ei and epi plasmas. It is important to note that shear flow is responsible for the linear instability.…”
mentioning
confidence: 99%